2014
DOI: 10.1007/978-3-319-04981-6_6
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Perfusion Computed Tomography (PCT) Imaging After Aneurysmal Subarachnoid Hemorrhage: A Review of the Current Data

Abstract: The present review demonstrates that PCT imaging is able to detect EBI as well as DCI in patients experiencing aSAH. As a consequence, this technique should be routinely implemented in monitoring strategies for this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…A limitation of the present method presented here is that it can only be used to quantify vasospasm of cerebral vessels, but does not allow conclusions concerning other factors leading to DCI. More pathophysiological information could be provided in future experimental studies by in vivo micro-CTP and in vivo micro-CTA in murine and other rodent models of SAH, as CTP is well established in this context in clinical practice [ 27 30 ]. A recent study performed in vivo high resolution digital subtraction angiography [ 31 ] and cerebral CTA of the murine cerebrovasculature [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the present method presented here is that it can only be used to quantify vasospasm of cerebral vessels, but does not allow conclusions concerning other factors leading to DCI. More pathophysiological information could be provided in future experimental studies by in vivo micro-CTP and in vivo micro-CTA in murine and other rodent models of SAH, as CTP is well established in this context in clinical practice [ 27 30 ]. A recent study performed in vivo high resolution digital subtraction angiography [ 31 ] and cerebral CTA of the murine cerebrovasculature [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the combination of the automated detection of vasospasm on CTA and cerebral hypoperfusion on CTP was superior to assessments by either CTP or CTA alone for identifying patients with impeding cerebral infarction who underwent interventional DSA for vasospasm treatment to prevent this within 24 h. It remains difficult to identify the patients who would benefit from endovascular treatment of vasospasm. CTP has been shown to have good sensitivity and specificity for predicting angiographic vasospasm or cerebral infarction in SAH patients during the course of the disease (13)(14)(15)(16)(17)(18); however, a prospective study reported that CTP had a PPV of only 29% for predicting severe vasospasm or a new cerebral infarction within the subsequent 72 h (19). Another study reported that a combination of vasospasm identified by CTA together with an increased mean transit time on CTP was the most accurate method for predicting vasospasm as identified by DSA (20).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in many clinical centers (including ours), the decision on whether or not to perform endovascular vasospasm treatment is based on the clinical symptoms, combined with CTP to detect cerebral hypoperfusion and CTA to estimate the extent of angiographic vasospasm. However, while the CTP evaluation is based on rather objective parameters and scores (13)(14)(15)(16)(17)(18)(19), there is a lack of corresponding objective parameters for the evaluation of CTA, resulting in a considerable degree of subjectivity and investigator dependence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations